The Existence of the Saleum Movement in Aceh Traditional Dance - Tri Supadmi; Lindawati Lindawati; Ismawan Ismawan; Helmunira Mahdi (Proceedings of AICS - Social Sciences, 2021)
There are several types of traditional dances in Aceh, including the Pho dance, Seudati dance, Rapa'i Geleng dance, Laweut dance and Likok Pulo dance. Each dance has a different saleum movement position. Based on the various kinds of dance, the researcher conducted a research on how the existence of saleum movement in Acehnese dances is. The purpose of this study is to describe how the existence of the saleum movement in Acehnese dances is. The type of research used is descriptive, the resource persons in this study are Imam Juaini, an artist and Chairperson of Saleum Community, Cut Mala Hayati, the Chairman of the Studio Putroe Jeumpa Keubiru and Acehnese traditional dancers. The techniques of data collections were interview, observation and documentation. The results showed that the Saleum movement in the traditional dance Pho was at the beginning of the dance. Saleum movement in the form of both hands raised in a half-chested prayer position. Saleum movement in the traditional dance Seudati is after the configuration of the opening act line. Saleum movement in the traditional dance Rapa'i Geleng is done after Seulaweut, the players enter the stage by walking while chanting prayers. The floor design forms one shaf (row), sitting in a row facing the front. Saleum in the traditional dance Likok Pulo is at the beginning of the dance opening by sitting neatly in a row of one row facing the front.Keywords: Acehnese Dances, Saleum Movement, Existence.